Disposition of emergency department patients with psychiatric comorbidity: results from the 2004 National Hospital Ambulatory Medical Care Survey. Issue 4 (20th March 2006) - Kunen, S; Prejean, C; Gladney, B; Harper, D; Mandry, C V
Abstract : Background: Few emergency department (ED) studies have examined how psychiatric comorbidity relates to hospitalisation decisions. Methods: We assessed the relationship of psychiatric comorbidity to hospitalisation decisions among ED patients in the 2004 National Hospital Ambulatory Medical Care Survey. Results: Patients with psychiatric comorbidity were five times more likely to be hospitalised than patients with a single psychiatric diagnosis. The most frequent psychiatric comorbidities involved substance use disorders (SUDs). Conclusions: Psychiatric disorders are underdiagnosed among ED patients. We believe that this underdiagnosis may be partly responsible for the high hospitalisation rates of ED patients with SUDs